Characterization of the diversity and metabolic potential of hypolithic communities in dronning Maud Land, Antarctica - Mikhari, Rito Leanah (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Access restricted until April 2022.
Keywords: Uncatalogued